2000
DOI: 10.1002/1096-9071(200012)62:4<435::aid-jmv7>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Increased immunoglobulin G, but not M, binding to endogenous retroviral antigens in HIV-1 infected persons

Abstract: The modes of interaction between products of human endogenous retroviral (HERV) sequences and the immune system are largely unknown. In HIV infected persons, an exogenous retrovirus adds further complexity to the situation. Therefore, 14 synthetic peptides with sequences derived from conserved regions of various endogenous retroviruses (ERVs) and from related exogenous retroviruses were used to search for IgG and IgM antibodies that bind to such antigens in 15 HIV-1 seropositive and 17 seronegative immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Human IgG reactivity to MLV capsid has been reported previously [59], [60]. In one study, a higher frequency of individuals with MLV capsid-reactive IgG was seen with HIV-1 infection compared to HIV-1 negative controls, a trend we did not observe with this cohort [59]. Nonetheless, proteins encoded by HERVs represent a potential source of antigen that may give rise to antibodies that are cross-reactive with XMRV.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Human IgG reactivity to MLV capsid has been reported previously [59], [60]. In one study, a higher frequency of individuals with MLV capsid-reactive IgG was seen with HIV-1 infection compared to HIV-1 negative controls, a trend we did not observe with this cohort [59]. Nonetheless, proteins encoded by HERVs represent a potential source of antigen that may give rise to antibodies that are cross-reactive with XMRV.…”
Section: Discussionsupporting
confidence: 49%
“…It is possible that the positive signals obtained in our immunoblots are due to the presence of cross-reactive antibodies to proteins encoded by human endogenous retroviruses (HERVs), a large group of which is similar to MLVs [57], [58]. Human IgG reactivity to MLV capsid has been reported previously [59], [60]. In one study, a higher frequency of individuals with MLV capsid-reactive IgG was seen with HIV-1 infection compared to HIV-1 negative controls, a trend we did not observe with this cohort [59].…”
Section: Discussionmentioning
confidence: 63%
“…Fourteen peptides derived from various endogenous retroviruses were used to search for IgM and IgG antibodies in HIV-1 infected and uninfected immunosuppressed persons by Lawoko et al . [78]. Three peptides, corresponding to the C-terminal half of the murine leukaemia virus capsid protein, a conserved domain of the HERV-H transmembrane domain, and part of HERV-K HML-3 encoded Pol, were found to bind IgG in both groups, with stronger binding of the latter two peptides in HIV-1 infected patients [78].…”
Section: Herv Proteins and Antibodies In Hiv Infected Patientsmentioning
confidence: 99%
“…HSV-1 and the influenza virus have been shown to modulate LTR activity of HERV-W while HERV-K LTR activity was positively modulated by the influenza A/WSN/44 strain [1921]. A number of studies have also highlighted an increase in the expression of mostly HERV-K family members in HIV-1-infected patients, thereby leading to a CTL response toward HERV proteins [2830]. An in vitro study has further shown that HIV infection leads to increase in HERV-K expression [31].…”
Section: Resultsmentioning
confidence: 99%